Transmissible Gastroenteritis (T.G.E.) of piglets. Field diagnostic techniques - ΚΥΡΙΑΚΗΣ ΣΠ. Κ.; ΑΝΔΡΕΩΤΗΣ Σ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The authors describe three diagnostic techniques, namely the visual diagnostic technique, the measurement of pH of colonic contents and the detection of Lactase activity, to differentiate TGE from collibaciliosis in the field, and the practica! personal experience by the use of above methods. The final conclusion is that the visual technique is the method of choice. The visual diagnostic technique is simple and gives very good results. The measurement of the pH must be combined with any of other two methods. Demonstration of Lactase activity, or its absence, though accurate as a method, requires laboratory facilities.